Épocas de semeadura e cultivares de soja em áreas de terras baixas na fronteira oeste - (:unkn) unknown (Universidade Federal do Pampa, 2023)
Soybean (Glycine max) is one of the most cultivated crops in the world, showing its great importance in the food market. In Rio Grande do Sul, the production of this legume in lowland areas is gaining great expression, which brings great development to the West Frontier region, and may be a good option for crop rotation and the recovery of areas degraded by the intense rice production in the region. The objective of this work was to determine the yield components of five soybean cultivars in three sowing dates. The work was carried out in the experimental area of Unipampa (Federal University of Pampa - Campus Itaqui/RS). The experimental design used was randomized blocks with five plots and three replications. In the treatments, five soybean cultivars were used, selected because they represent different GMR, which is directly associated with the size of the cultivar cycle and in two sowing times of the culture. Subsequently, the following materials were selected, C2531 E, DM 5958 IPRO, BS 2606 IPRO, Brasmax GARRA IPRO and DM 66168 IPRO, with their respective GMR in the same order (5.3; 5.8; 6.0; 6.3 and 6.8). Sowings were carried out on 10/27/2021, 11/18/2021 and 12/10/2021 and emergence occurred on 10/31/2021, 11/23/2021 and 12/18/2021 for the five cultivars. Soybean productivity decreases as sowing is delayed, regardless of the GMR used. The height of the insertion node of the first legume is reduced according to the use of cultivars with a lower degree of relative maturation. Plant height is reduced as the sowing date is delayed and therefore also reduced as the GMR of the cultivars is reduced. The cycle of cultivars is reduced according to the delay in the sowing date.
Sowing times and soybean cultivars in lowland areas in the western frontier
Keywords: Glycine max.; Ciclo; Grau de Maturação Relativa; Cycle; Degree of Relative Maturation; CNPQ::CIENCIAS AGRARIAS